EDUKASI PENGGUNAAN CAREER DEVELOPMENT THEORIES DALAM MEMBANTU SISWA MENETAPKAN PILIHAN JURUSAN ILMU EKONOMI DI PERGURUAN TINGGI - Samsuddin, M. Afdal; Fitriyanti, Eka; Putra, Agung Rizki (Universitas Mataram, 2024)
Vocational High Schools (SMK) have a very important role in the Indonesian education system. SMKs are essential for equipping students with the knowledge and practical skills needed to enter the world of work, such as provision of employability skills, providing educational alternatives, increasing employment opportunities, collaboration with industry, encouraging entrepreneurship, and educational inclusion. SMK Negeri 1 Sungailiat is a leading vocational school dedicated to providing quality education in various fields, such as economics. The choice of major is an important first step for SMK students in building their careers. However, deciding on a major that matches interests, talents, and career goals can be difficult, especially for students who do not yet understand careers in economics. Career Development Theories is a conceptual framework that describes how individuals make career choices, develop themselves, and move forward in their careers throughout life. These theories help us understand the factors that influence career decision-making, the process of career identity formation, and one's professional development from childhood to retirement. The purpose of this activity is to apply CDT to SMK Negeri 1 Sungailiat students to help them choose a major in economics, as well as see how students' perceptions of the economist profession are influenced by self-efficacy beliefs, expected outcomes, and personal goals. The results achieved through community service activities are documented in a report on the implementation phase which includes the initial visit, preparation, and education. For future development plans, educating students in determining their choice of economics major is very important to implement Career Development Theories.